PELATIHAN APLIKASI AKADEMIK RAPOR ONLINE BERBASIS WEB SEBAGAI ALAT BANTU MONITORING HASIL BELAJAR SISWA (STUDI KASUS: MADRASAH ALIYAH NEGERI 12 JAKARTA) - Hendra Jatnika; Muhammad Farid; Yessy Fitriani; Rakhmadi Putra Irfansyah; Dine Tiara Kusuma; Yoga Distira Sudirman; Yudi Setyo Purwanto; Amanda T Supriadi (Terang, 2019)
In order to suppor the government’s efforts at advancing the people’s prosperity and to make an educated the nation, and also to make one of the missions of STT-PLN to improve the education, research, and community service activities, the P2M team has an agreement to improve the education services at MAN 12 Jakarta. As the continuity of the previous P2M, the team focuses on the training of the web-based online report administrators. This application was built by the team and called SIRO MADU, an abbreviation of Sistem Informasi Rapor Online Terpadu. The goal of the P2M is to help the MAN 12 Jakarta to adapt and make use of the information technology development to ease some process which was manually done before, which at the end will im prove the service quality of the MAN 12 Jakarta. The target is to make MAN 12 Jakarta to be able to implement and has the ability to operate and manage the SIROMADU application program. It will also train the administrator of information technology department at MAN 12 Jakarta.